METODE PEMBELAJARAN TAHSIN DALAM PENINGKATKAN KETERAMPILAN MEMBACA AL-QUR’AN DI SMPN 5 PALOH KABUPATEN SAMBAS - Ariska, Elsa (ILJ: Islamic Learning Journal, 2023)
Every Muslim has an obligation to learn to read the Qur'an and teach it. Middle School (SMP) Negeri 5 Paloh, Sambas Regency continues to strive to improve students' ability to read the Qur'an by applying the Al-Qur'an tahsin learning method. This study uses a qualitative approach with the type of research used is a case study. The results of the study show that: 1. Planning for tahsin learning to improve Al-Qur'an reading skills for students at SMPN 05 Paloh, includes a) Analysis of students' initial abilities, b) Formulating specific objectives for learning tahsin, c) Development of competency standards and basic competencies tahsin, d) Developing tahsin learning materials, e) Developing tahsin learning strategies; f) Determine the people involved in the tahsin learning process, g) Develop tahsin learning media, and h) Develop tahsin learning assessments. 2). The application of the tahsin method to improve Al-Qur'an reading skills for SMPN 05 Paloh students is: a) Preparation, namely finding a comfortable time, atmosphere and place in the learning process, reading a prayer before starting learning, setting out learning objectives, preparing volumes or the Koran and writing tools for educators to explain, prepare a value summary book to see students' progress in reading the Qur'an, b) The main part of the lesson, namely the teacher conveys Al-Qur'an material in stages from easy to understand to rather difficult according to the participants' intelligence abilities students, educators ask students to repeat reading so that students practice more so that it will be easier to master reading; educators ask students to come forward to practice reading the Al-Quran according to what is in the Al-Quran Hadith book according to the correct tajwid reading, the educator listens and immediately gives a warning if there are students who are wrong in reading the Al-Quran, and the educator gives an evaluation and gives overall enthusiasm to provide reinforcement, and c) The final part, namely informing students of upcoming material and the educator closes the lesson by saying hamdalah or prayer.